Thromboembolism arterial feline – literature review - Canei, D. H.; Kataoka, A. (Scientific Electronic Archives, 2018)
Thromboembolism is characterized by the obstruction of a vessel caused by a blood clot formed elsewhere and transported with the bloodstream. This syndrome occurs in felines and is usually associated with hypertrophic cardiomyopathy, facilitating the formation of thrombi in the interior of the atrium or left ventricle. It occurs more frequently in middle aged male cats with no defined breed, probably because they are most affected by cardiomyopathy. Clinical signs are usually acute, secondary to tissue ischemia, and are related to the site of obstruction. The diagnosis is based on the characteristics found in the physical examination and anamnesis, with frequent paralysis of acute pelvic limbs, cold limbs and cyanotic cushions. Treatment consists of preventing the formation of new thrombi, improving pain, controlling hypertrophic cardiomyopathy or severe arrhythmias and supportive treatment.